INFORMATIVE SAFETY AS MEANS OF COUNTERACTIONS OF CYBERCRIME - Baimakhanov Уалихан Бексултанович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
In this article problems of informative safety in Kazakhstan examine as means of counteractions of cybercrime. Also the negative factors that restrain active fight with cybercrime are marked.